A strontium isotope and trace element geochemical study of dolomite-bearing bentonite deposits in Bavaria (Germany). (1st May 2017) - Köster, Mathias; Hölzl, Stefan; Gilg, H. Albert
The Landshut bentonites that formed from Ca- and Mg-poor rhyolitic tuffs in a fluviatile-lacustrine depositional environment of the Miocene Upper Freshwater Molasse, southern Germany, contain abundant palustrine, pedogenic and groundwater carbonates. Geochemical analyses of dolomites, calcites and smectites from bentonites of various environments by X-ray diffraction, thermal ionization mass spectrometry, inductively coupled plasma-mass spectrometry, and handheld X-ray fluorescence yield new insights into the compositions of fluids and sources of imported components involved in carbonate formation and bentonitization, as well as the timing of bentonite formation. Evaporated, Sr-rich brackish surface water with a molar Mg/Ca ratio of 2–5, derived mostly from the weathering of detrital carbonates, was involved in dolomite and bentonite formation in palustrine and some pedogenic environments. However, Sr-poor groundwater with a molar Mg/Ca ratio of ∼ 1 and a stronger silicate weathering component caused bentonite and calcite formation in strictly pedogenic and groundwater settings. The 87Sr/86Sr and molar Mg/Ca in the smectite interlayers indicate later cation exchange with water having more radiogenic Sr sources and smaller molar Mg/Ca ratios. The Rb-Sr data indicate the common presence of detrital illitic phases in the <0.2 μm fractions of the bentonites. Cogenetic palustrine dolomite and a single smectite residue sample which lacks this detrital illitic phase provide an age constraint for bentonitization at 14.7 ± 4.1 Ma identical to primary ash deposition. Thus a rapid onset of bentonitization of accumulated ash and dolomite formation in evaporation-driven wetland environments is indicated for the genesis of the Landshut bentonites.